Estimates of avian collision with power lines and carcass disappearance across differing environments. (17th August 2016) - Costantini, D.; Gustin, M.; Ferrarini, A.; Dell'Omo, G.
Abstract: Data on collisions of birds with high‐voltage electric power lines are scarce and are often gathered without protocols for the correction of carcass disappearance. There is actually growing awareness that it is important to accomplish carcass removal trials in order to develop correction factors for producing adjusted estimates of mortality due to collisions. In this study, we provided for the first time raw counts and estimates of bird collisions across seven Italian areas that largely differ in their habitats. We also carried out carcass removal trials to compute the rate of carcass disappearance and produce better estimates of collision events and of optimal time intervals of carcass searches. Results of 1‐year monitoring showed a general low frequency of birds collided with the power lines. Carcass removal trials showed effects of carcass size and season on the carcass disappearance, which varied largely among the study areas. In four areas, both small and large carcasses had more than 50% probability to be removed within 3–5 days from their distribution. Given the high variation among study areas, we suggest that estimates of carcass persistence and optimal time intervals should be conducted concurrently for each new study site. Abstract : Our article provides for the first time raw counts and estimates of bird collisions with high‐voltage power lines across seven Italian areas, and estimates of carcass disappearance that will help to improve monitoring programmes of fatal collisions of birds with the power lines.